A nonhuman primate model of blue light-induced progressive outer retina degeneration showing brimonidine drug delivery system-mediated cyto- and neuroprotection. (August 2021) - Rajagopalan, Lakshmi; Ghosn, Corine; Tamhane, Mitalee; Almazan, Alexandra; Andrews-Jones, Lydia; Kulkarni, Ashutosh; Christie, Lori-Ann; Burke, James; López, Francisco J.; Engles, Michael
Abstract: Geographic atrophy (GA) is an advanced form of age-related macular degeneration (AMD) characterized by atrophy of the retinal pigment epithelium (RPE), loss of photoreceptors, and disruption of choriocapillaris. Excessive light exposure is toxic to the retina and is a known risk factor for AMD. We first investigated the effects of blue light-induced phototoxicity on RPE and photoreceptors in nonhuman primates (NHPs, a model of progressive retinal degeneration) and then evaluated the potential cyto- and neuroprotective effects of the brimonidine drug delivery system (Brimo DDS). In the first set of experiments related to model development, parafoveal lesions of varying severity were induced using blue light irradiation of the retina of cynomolgus monkeys to evaluate the level of phototoxicity in the RPE and photoreceptors. RPE damage was assessed using fundus autofluorescence imaging to quantify areas of hypofluorescence, while thinning of the outer nuclear layer (ONL, photoreceptor nuclei) was quantified using optical coherence tomography (OCT). Photoreceptor function was assessed using multifocal electroretinography (mfERG). RPE damage progressively increased across all lesion severities from 2 to 12 weeks, as did the extent of ONL thinning. Lesions of high severity continued to show reduction in mfERG amplitude, reaching a statistically significant maximum reduction at 12 weeks. Collectively, the first set of experiments showed that blue light irradiation of the NHP eye resulted in progressive retinal degeneration identified by damage to RPE, ONL thinning, and disrupted photoreceptor function – hallmarks of GA in humans. We then used the model to evaluate the cyto- and neuroprotective effects of Brimo DDS, administered as a therapeutic after allowing the lesions to develop for 5 weeks. Placebo DDS or Brimo DDS were administered intravitreally and a set of untreated animals were used as an additional control. In the placebo DDS group, hypofluorescence area continued to increase from baseline, indicating progressive RPE damage, while progression was significantly slowed in eyes receiving Brimo DDS. Likewise, ONL thinning continued to progress over time in eyes that received the placebo DDS, but was reduced in Brimo DDS-treated eyes. Pharmacologically relevant brimonidine concentrations were sustained in the retina for up to 26 weeks following Brimo DDS administration. In summary, Brimo DDS demonstrated cyto- and neuroprotective effects in a novel NHP GA model of progressive retinal degeneration. Highlights: Blue-light phototoxicity in the NHP retina mimics geographic atrophy in human AMD. Brimonidine DDS has cyto- and neuroprotective effects in RPE and photoreceptors. Sustained concentrations of brimonidine had beneficial effects in the retina.